Benchmarking the Performance of AES and ECC Encryption for Secure Digital Communication in Cloud Systems - Damas Alfiqhyanto; Eka Ardhianto (Universitas Islam Indragiri, 2026)
This study compares the performance of the Advanced Encryption Standard (AES) and Elliptic Curve Cryptography (ECC) for securing digital communications in cloud computing environments. A quantitative experimental-comparative approach was employed using a counseling conversation dataset comprising 9,036 valid records. The dataset was divided into five quintiles based on text length (number of characters), from which 1,805 samples were selected through stratified random sampling. The experiments were conducted in Google Colab using Python 3.10, and the algorithms were evaluated in terms of encryption and decryption time, throughput, CPU utilization, memory consumption, and ciphertext entropy. The results indicate that AES outperformed ECC in computational efficiency, achieving an average encryption time of 0.00013 seconds while requiring only 0.83–0.86 kB of memory. In contrast, ECC demonstrated superior suitability for secure key exchange despite its higher computational overhead. These findings suggest that AES is the preferred choice for efficient data encryption in cloud-based digital communication systems, whereas ECC is more appropriate for cryptographic key exchange in applications requiring a higher level of security.